Effect of Alpha Lipoic Acid on Cognitive Function in Normoglycaemic Mice - Idris Bello, Aishatu; Zakari Ibrahim, Amina; Zubairu Yakubu, Zainab; Umar Kura, Aminu; Aliyu Ladan, Ahmad; Hassan Garkuwa, Adamu; Ibrahim, Buhari; Bello Yakubu, Adamu; Adamu Garkuwa, Usman; Zakari Ibrahim, Amina (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Neuronal cells depend on glucose as their main source of energy and persistent hyperglycaemia has been shown to affect it. Researchers have investigated the influence of hyperglycaemia on memory in diabetic animals. Both the pathogenesis of memory impairment as well as the progression of the disease was influenced by hyperglycaemia. This research evaluated the effect of alpha lipoic acid on memory in normoglycemic mice. Twenty (20) Swiss albino mice were used for the study and divided into four groups of five (n = 5) each. Group I received normal saline (10 ml/kg) while groups II, III and V received glibenclamide (2 mg/kg), alpha lipoic acid (200 mg/kg) and alpha lipoic acid (400 mg/kg). Working memory was determined using spontaneous alternation in the Y maze and social memory was determined using a novel object recognition task. Results showed that alpha lipoic acid at the two doses (200 mg/kg and 400 mg/kg) after administration for fourteen (14) days did not improve spatial working memory in the Y maze test and discriminative index in novel object recognition task when compared to day 0 (pre-treatment). Also, recognition memory showed no significant (p > 0.05) change compared to the control group. Other doses of alpha lipoic acid do not significantly improve spatial working memory and recognition memory in the Y maze test and novel object recognition task. Alpha lipoic acid improved spatial working memory and discriminative index and showed no effect on recognition memory in normoglycaemic mice.